1D Versus 2D Site Effects from Numerical Analyses on a Cross Section at Barberino Di Mugello (Tuscany, Italy). (2016) - Madiai, Claudia; Facciorusso, Johann; Gargini, Elisa; Baglione, Massimo
Abstract: The results of 1D and 2D numerical analyses performed to better understand the basin geometry effects on ground seismic response in a site of the Mugello area are presented and discussed. Geological subsoil modelling and site geotechnical characterization were performed by using the results of extensive surveys carried out in the area within in-depth seismic microzonation studies promoted by Regional Government of Tuscany. The selected section has a quite regular and horizontal ground profile so that the topographic effects are negligible with respect to the basin effects due to the buried valley. With the aim of distinguishing morphological ('edge effects') from stratigraphic effects, the results from 2D analyses were compared to those from 1D numerical modelling on a large number of vertical soil profiles spaced along the examined cross-section. Different amplification factors were considered with reference to both peak ground acceleration and elastic response spectra.